Controlled low strength material with industrial by-products in the isolation of contaminated sites - J. Sumalatha; M. C. Nataraja; G. L. Sivakumar Babu (International Journal of Sustainable Engineering)
Contaminated lands at significant depths require proper isolation systems to prevent the migration of pollutants. Traditional concrete cut-off walls are expensive and challenging to construct owing to slow strength development and structural integrity issues. A flowable fill, such as a Controlled Low-Strength Material (CLSM), provides an ideal alternative because of its ease of construction and quick strength gain. This study aims to replace conventional concrete with CLSM for cut-off walls designed to retard leachate seepage from polluted lands or landfills. To promote sustainability, waste materials such as arecanut fibre, crumb rubber, and coconut fibre are incorporated into CLSM. Unconfined compression tests revealed that the optimal CLSM mix consisted of a 1:10:25 ratio of cement, fly ash, and sand combined with 5% rubber, 0.2% arecanut fibre, and 0.2% coconut fibre. Cut-off wall models were prepared with this mixture and black cotton soil, and chemical solutions of Cu, Zn, Ni, Fe, and Ca were allowed to pass through these model cut-off walls to check their capacity to retard the migration of pollutants. The effluent concentrations over time were plotted, and the results revealed that the identified CLSM material effectively retarded the migration of metal ions, making it suitable for cut-off wall construction.